Juegos tradicionales y su incidencia en el desarrollo físico y mental de los niños y niñas de primer año de Educación Básica de la Unidad Educativa Juán León Mera del Cantón Quevedo, año 2015 - Pesantes Ramos, Erika Katiuska (2015)
This thesis refers "TRADITIONAL GAMES AND ITS IMPACT ON THE PHYSICAL AND MENTAL DEVELOPMENT FOR CHILDREN OF FIRST YEAR OF BASIC EDUCATION Education Unit CANTON JUAN LEON MERA QUEVEDO, 2015.". It was raised for research a general objective: To determine how traditional games affect the physical and mental development of children in the first year of basic education Education Unit Juan León Mera Canton Quevedo of the school year 2015. The framework consists of research and literature based on the field of basic education on knowledge, being live, do. The variables defined as potentiating tool procedures and benefits of possible solutions, as focuses weak processes of teachers in terms of pedagogical management of children. The methods used for the preparation of this research study were: inductive, deductive, analytic-synthetic, Descriptive; the techniques used were: a survey of teachers and the Director of the institution to identify the types of traditional games made in the daily work with children and in the same way they applied the survey to Parents Family of children first year of basic education educational Unit Juan León Mera canton Quevedo of the school year 2015 to determine the socio-emotional development of their children.